2015
DOI: 10.1021/acs.energyfuels.5b00876
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of the Chemical Reaction of Carbon Dioxide with Ionic Liquids and Amines in Ionic Liquid Solution

Abstract: This paper focuses specifically on certain ionic liquids which are capable of acting as chemisorbents for CO2 at ambient pressure and temperature. This low pressure approach based on chemical reactivity is more effective than traditional physical absorption / solubility approaches for CO2 capture in ionic liquids for higher pressure carbon capture. We describe a class of imidazolium ionic liquids bearing a relatively acidic hydrogen atom at C-2 which upon initial abstraction develops a nucleophilic carbon atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…has been reported previously by Besnard et al (2012) and Kortunov et al (2015), who showed that the signal at 141.5 ppm corresponds to the carboxylated C3 position in EMIM ? .…”
Section: Chemical Structures Of Dissolved and Regenerated Cellulosesupporting
confidence: 68%
See 1 more Smart Citation
“…has been reported previously by Besnard et al (2012) and Kortunov et al (2015), who showed that the signal at 141.5 ppm corresponds to the carboxylated C3 position in EMIM ? .…”
Section: Chemical Structures Of Dissolved and Regenerated Cellulosesupporting
confidence: 68%
“…These findings indicate that a possible reaction takes place between the cellulose-sorbed CO 2 and the EMIM?, yielding a carboxylated EMIM ? with characteristic NMR signals (Besnard et al 2012;Kortunov et al 2015) coincident with the signals observed at 154.3 and 141.5 ppm. It is, however, important to bear in mind that the carbonate band seen in the ATR-IR spectroscopy in which no EMIMAc was present shows that the signal at 154.3 ppm does not originate from the EMIMAc but is introduced during the dissolution of cellulose in NaOH(aq).…”
Section: Chemical Structures Of Dissolved and Regenerated Cellulosesupporting
confidence: 62%
“…The formation of the ylide complex by the deprotonation step is the crucial factor for the chemisorption of CO 2 by the cation. In previous 44 work, the authors did not report the transition states of the chemisorption reaction of CO 2 by ylide complex as well as an anion. However, we found the transition states for both the pathways and the formation of the ylide complex are the most energetic processes.…”
Section: Resultsmentioning
confidence: 99%
“…consequence of these different reaction pathways, and the motivation for the amine work described in this and related publications, 1,49,50 is that theoretical CO 2 sorption capacity for an amine system is a function of the products that are formed. When ammonium carbamates are the preferred reaction product under non-aqueous conditions, the theoretical CO 2 sorption capacity is only 50 mol% per amine (2:1 amine:CO 2 ratio).…”
Section: Reaction Chemistry Of Amine/co 2 Sorptionmentioning
confidence: 99%